STRATEGI DIGITAL MARKETING BERBASIS AI DAN PERSONALISASI KONTEN UNTUK MENINGKATKAN CUSTOMER ENGAGEMENT DI ERA GEN Z - Thessalonica S.F. Supit; Luckhy Natalia Anastasye Lotte; Elmiwati (CV. Lafadz Jaya, 2026)
This article discusses digital marketing strategies based on artificial intelligence (AI) and content personalisation to enhance customer engagement in the Gen Z era. This study is motivated by changes in the behaviour of young consumers, who are becoming increasingly selective, critical and responsive to digital content that is relevant, authentic and interactive. This research employs a literature review method, examining various academic sources relating to AI in digital marketing, content personalisation, and the behavioural characteristics of Gen Z. The findings indicate that AI plays a crucial role in consumer data analysis, marketing automation, content recommendations, and real-time interactions, whilst content personalisation strengthens the emotional connection between brands and their audience. The combination of these two approaches has proven capable of enhancing customer engagement through content that is more relevant, targeted and tailored to the preferences of the younger generation. However, the implementation of this strategy still requires attention to ethical considerations, data privacy and transparency regarding the use of technology. Consequently, AI-based digital marketing and content personalisation represent a strategic approach to building stronger and more sustainable customer engagement in the Gen Z era.